2011
DOI: 10.1016/j.rmed.2011.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopy in suspected pulmonary TB with negative induced-sputum smear and MTD® Gen-probe testing

Abstract: Bronchoscopy provided diagnostic confirmation of pulmonary TB in 10% of subjects at least 2 negative induced-sputum samples by smear microscopy and NAA testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 38 publications
5
24
0
Order By: Relevance
“…However, bronchoscopy has an integral part in the diagnosis of negative smear MTB patients. Previous studies revealed a wide range of bronchoscopy diagnostic yield in negative smear TB patients, which was reported as low as 10% [ 17 - 18 ]. In our study, MTB diagnosis was confirmed in 37.7%, higher than previous studies, yet lower than reported by Alzeer et al (67%) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, bronchoscopy has an integral part in the diagnosis of negative smear MTB patients. Previous studies revealed a wide range of bronchoscopy diagnostic yield in negative smear TB patients, which was reported as low as 10% [ 17 - 18 ]. In our study, MTB diagnosis was confirmed in 37.7%, higher than previous studies, yet lower than reported by Alzeer et al (67%) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although different opinions have been expressed regarding the importance of the source and type of test sample ( Bunyasi et al, 2015 ), the quality of the specimen has been considered as a determinant factor affecting assay performance ( Pinto and Udwadia, 2013 ). Theron et al (2014) found that expectorated sputum was the best specimen with the highest sensitivity among all pulmonary specimens including BALF, possibly due to the highest bacterial load of the sputum that has been expectorated properly ( Iyer et al, 2011 ; Theron et al, 2014 ). However, unacceptable quality of sputum samples received by diagnostic laboratories is a common issue in China and worldwide and has become a significant cause of low diagnostic yield ( Heineman et al, 1977 ; Macq et al, 2005 ; Ou et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…We suspected that the current inadequacies in sputum collection in the two hospitals that participated in this study might have led to insufficient quality of expectorated sputum used for testing and consequentially may have affected the performance of all diagnostic assays. In the two hospitals, bronchoscopy and BALF are routinely recommended for patients who are sputum-scarce or have negative sputum smear-microscopy and Xpert MTB/RIF, while their clinical and radiological examinations are highly suggestive of pulmonary TB, or for differential diagnosis to clarify the underlying cause of a radiographic abnormality ( de Gracia et al, 1988 ; Iyer et al, 2011 ). When a head-to-head comparison was carried out between BALF and expectorated sputum obtained from the same patients at the same time point to avoid sampling bias, BALF was found to be superior to expectorated sputum in diagnosing pulmonary TB in the population sampled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, only five of 24 patients (20.8%) who failed early diagnosis with IS underwent bronchoscopy in this study, the addition of bronchoscopy enabled early diagnosis of PTB in 60% (3 of 5) and increased bacteriologically confirmed diagnosis rate in 20% (1 of 5) ( Table 2 ). Iyer et al 26 also showed that bronchoscopy provided diagnostic confirmation of PTB in 10% of patients suspected with PTB with negative IS smear and TB-PCR results. Thus, bronchoscopy may be useful for a rapid and accurate diagnosis of PTB when IS smear and TB-PCR are negative.…”
Section: Discussionmentioning
confidence: 98%